The effect of entrepreneurship education on the determinants of entrepreneurial behaviour among higher education students: A multi-group analysis - Shahzada Adeel; Ana Dias Daniel; Anabela Botelho (Journal of Innovation & Knowledge (JIK), 2023)
Entrepreneurship is generally considered the engine of social and economic development. Therefore, its promotion is of the utmost importance, especially in a context of crisis, such as the one currently experienced due to the COVID-19 pandemic. In order to identify the best approaches to foster entrepreneurship, this study aims to understand how entrepreneurship education impacts the development of entrepreneurial skills and behaviors in students. The results of this study show that the behavior associated with promoting new ventures can be predicted by specific individual characteristics. More specifically, individuals with greater prior knowledge, entrepreneurial alertness, opportunity recognition, entrepreneurial motivation, and entrepreneurial intention exhibit greater entrepreneurial behavior. In addition, the results of the multi-group analysis indicate that the proposed model works differently in students with some type of entrepreneurship training and in those with none. More specifically, students enrolled in entrepreneurship education are more likely to use prior knowledge and alertness to recognize new business opportunities and align their motivations toward starting a new venture than other students.
Keywords: 650; Entrepreneurial behavior; Entrepreneurial intention; Entrepreneurial motivation; Entrepreneurship education; Entrepreneurship: entrepreneurial alertness; Opportunity recognition